Five-year experience with the peri-operative goal directed management for surgical repair of traumatic aortic injury in the eastern province, Saudi Arabia - Haytham Z Al-Gameel (Saudi Journal of Anaesthesia, 2014)
Context: Traumatic aortic injury (TAI) accounts for 1/3 of all trauma victims. Aim: We aimed to investigate the efficacy of the adopted standardized immediate pre-operative and intra-operative hemodynamic goal directed control, anesthetic technique and organs protection on the morbidity and mortality in patients presented with TAI. Settings and Design: An observational retrospective study at a single university teaching hospital. Materials and Methods: Following ethical approval, we recruited the data of 44 patients admitted to the King Fahd Hospital of the University, Al Khobar, Saudi Arabia, with formal confirmation of diagnosis of blunt TAI during a 5-year period from February 2008 to April 2013 from the hospital medical records. Statistical Analysis: descriptive analysis. Results: A total of 44 victims (41 men, median (range) age 29 (22-34) years) with TAI who underwent surgical repair were recruited. Median (range) post-operative chest tube output was 700 (200-1100) ml necessitated transfusion in 5 (11.4%) of cases. Post-operative complications included transient renal failure (13.6%), pneumonia (6.8%), acute lung injury/distress syndrome (20.5%), sepsis (4.5%), wound infection (47.7%) and air leak (6.8%). No patient developed end stage renal failure or spinal cord injury. Median intensive care unit stay was 6 (4-30) days and in-hospital mortality was 9.1%. Conclusion: We found that the implementation of a standardized early goal directed hemodynamic control for the peri-operative management of patients with TAI reduces the post-operative morbidity and mortality after surgical repair.